Possibilities of Educating a Sense of Responsibility in Primary School Students - Abduganiyevich, Uzakov Ibodullo (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the socio-pedagogical interpretation of the concept of “responsibility”, the content of fostering a sense of responsibility in primary school students and organizational issues of fostering a sense of responsibility in primary school students. The focus is on ensuring that elementary school students have a sense of responsibility in the process of developing as individuals. The tasks of analyzing the concept of “responsibility” from a pedagogical point of view, substantiating its manifestations reflected in the actions and activities of the individual, fostering a sense of responsibility in primary school students are systematically analyzed. It also reflected the types of responsibilities that are essentially the same, as well as the ways in which elementary school students have a sense of responsibility. The expressed theoretical and practical ideas can be a valuable resource not only for primary school students, but also for educators working at different stages of education.